Adsorption of Ammonium Nitrogen from Aqueous Systems Using Chitosan-Bentonite Film Composite. (2016) - Haseena, P.V.; Padmavathy, K.S.; Krishnan, P. Rohit; Madhu, G.
Abstract: In this work, a novel composite adsorbent based on chitosan and bentonite nanoclay was prepared in the form of thin films and its efficacy for removing ammonium-nitrogen (NH4 + -N) from aqueous solution was investigated using batch adsorption experiments. The characterization of both chitosan and chitosan nanocomposite have been done with Thermogravimetric analyser and FTIR spectra. In the adsorption test, the effect of pH, initial concentration, and adsorbent concentration on NH4 + -N removal was studied. A comparison between as-prepared adsorbent and adsorbent modified with nanoclay was also carried out. The optimum condition for maximum adsorption of ammonia nitrogen from aqueous solution was found to be 15 ppm, 0.5 g, & 6 for initial concentration, adsorbent concentration and pH respectively. All information obtained gives an indication that the composite can be used as a novel type, fast-responsive and high-capacity sorbent material for NH4 + -N removal. As ammonium nitrogen is a good nutrient for plants and chitosan is a biopolymer the exhaust adsorbents can be reused as a fertilizer in agricultural purpose.